Do minimum wages improve self-rated health? Evidence from a natural experiment - Lucas Hafner (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2019)
In this paper I evaluate a labor market reform in Germany. In particular, I analyze whether the introduction of the general minimum wage in 2015 had an effect on self-rated health and labor market outcomes of individuals who were likely affected by the reform. I exploit the plausibly exogenous variation in hourly wages induced by the natural policy experiment and apply difference-in-difference analysis combined with propensity score matching. I use survey-data combined with administrative records which enables me to control for a vast set of possibly confounding variables. I find on average significant improvements of self-rated health for individuals who are affected by the reform. My analysis indicates, that reduced stress, due to a significant reduction of weekly working hours potentially drives this result.
Keywords: 330; minimum wage; self-rated health; natural experiment